Vale John Burke (1942–2023): A Tribute to a Man who Contributed Much to Australian Telecommunications, TelSoc, and to All of his Communities - Holmes, Jim (Journal of Telecommunications and the Digital Economy, 2023)
John Burke was a long-term member of TelSoc, a member of the Editorial Advisory Board of this Journal, and Convenor of TelSoc’s Broadband Futures Group. His sudden and unexpected death on 24 August 2023 was received with shock and great sadness by his colleagues in many fields, including in TelSoc and the ex-Telstra diaspora. This tribute focusses on John Burke’s substantial contribution over a long period to the telecommunications sector, but provides some indication of the other work that he did over his 81 years for the various communities of interest of which he was part. John believed in the power of informed communities to take action to improve society in terms of equitable outcomes and opportunity, and persistently acted on that principle.